2016
DOI: 10.14740/jocmr2466w
|View full text |Cite
|
Sign up to set email alerts
|

Focal Epithelial Hyperplasia (Heck’s Disease) in a 57-Year-Old Brazilian Patient: A Case Report and Literature Review

Abstract: Focal epithelial hyperplasia (FEH), or Heck’s disease, is a rare disease of the oral mucosa associated with infection by some subtypes of human papilloma virus, especially subtypes 13 or 32. The disease is predominantly found in children and adolescents with indigenous heritage, but other ethnic groups can be affected worldwide. To the best of the authors’ knowledge, it has not been reported in Brazil’s elderly population. This article describes a case of FEH in a 57-year-old Brazilian patient presenting since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
(42 reference statements)
0
14
0
6
Order By: Relevance
“…Medications, such as topical/systemic interferon and imiquimod cream, have demonstrated benefit in treating lesions of MEH 1 . Prognosis of MEH is indeterminate with risk of recurrence; however, malignant transformation has not been associated with the condition 1‐3 . This case highlights a rare presentation of MEH in a patient with an atypical racial background and age demographic for this condition.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Medications, such as topical/systemic interferon and imiquimod cream, have demonstrated benefit in treating lesions of MEH 1 . Prognosis of MEH is indeterminate with risk of recurrence; however, malignant transformation has not been associated with the condition 1‐3 . This case highlights a rare presentation of MEH in a patient with an atypical racial background and age demographic for this condition.…”
Section: Discussionmentioning
confidence: 94%
“…It has been suggested that HPV‐13 is more commonly associated with lesions found on keratinized epithelial mucosa, while HPV‐32 is more closely associated with lesions on non‐keratinized surfaces 1 . Genetic and environmental factors have also been implicated as risk factors for the condition 1‐3 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clínicamente se asemeja a una coliflor con una superficie digitiforme de base sésil y crecimiento lento, su coloración va del rosado al blanco dependiendo del grado de queratinización [33,34]. La hiperplasia epitelial multifocal o enfermedad de Heck es una enfermedad poco común que afecta principalmente a niños [35,36], se localiza en la mucosa bucal, labios o lengua y, clínicamente, se caracteriza por la presencia de pápulas múltiples que dan apariencia de "empedrado" de consistencia blanda y coloración similar a la mucosa adyacente, y es el vph serotipo 13 el asociado (véase la figura 1a) [37,38].…”
Section: B Lesiones Benignasunclassified
“…Heck's disease, or focal epithelial hyperplasia, is a rare benign disease of the oral mucosa associated with infection by human papillomavirus (HPV), subtypes 13 or 32. 1 It has been typically described in children and adolescents of indigenous heritage, specifically North, South, and Central American but has also been reported in immunosuppressed individuals, primarily in the setting of human immunodeficiency virus (HIV) infection. No gender predilection is found.…”
Section: Introductionmentioning
confidence: 99%